Lung Biopsy With a Non-intubated VATS Approach in an Obese Population: Indications and Results - Cherchi, Roberto; Ferrari, Paolo Albino; Guerrera, Francesco; Grimaldi, Giulia; Pinna-Susnik, Matteo; Murenu, Alessandro; Rosboch, Giulio Luca; Lybéris, Paraskevas; Ibba, Federica; Balsamo, Ludovica; Saderi, Laura; Fois, Alessandro Giuseppe; et al. (Frontiers in Surgery, 2022)
Background: According to the international guidelines, patients affected by interstitial lung disease with unusual clinical presentation and radiological findings that are not classic for usual interstitial pneumonia end up meeting criteria for surgical lung biopsy, preferably performed with video-assisted thoracic surgery. The growing appeal of non-intubated thoracic surgery has shown the benefits in several different procedures, but the strict selection criteria of candidates are often considered a limitation to this approach. Although several authors define obesity as a contraindication for non-intubated thoracoscopic surgery, the assessment of obesity as a dominant risk factor represents a topic of debate when minor tubeless procedures such as lung biopsy are considered. Our study aims to investigate the impact of obesity on morbidity and mortality in non-intubated lung biopsy patients with interstitial lung disease, analysing the efficacy and safeness of this procedure. Materials and Methods: The study group of 40 obese patients consecutively collected from 202 patients who underwent non-intubated lung biopsy was compared with overweight and normal-weight patients, according to their body mass index. Postoperative complications were identified as the primary endpoint. The other outcomes explored were the early 30-day mortality rate and intraoperative complications, length of surgery, postoperative hospitalization, patient’s pain feedback, and diagnostic yield. Results: The overall median age of the patients was 67.4 years [60, 73.5]. No 30-day mortality or significant differences in terms of postoperative complications (P = 0.93) were noted between the groups. The length of the surgery was moderately longer in the group of obese patients (P = 0.02). The postoperative pain rating scale was comparable among the three groups (P = 0.45), as well as the postoperative length of stay (P = 0.96). The diagnosis was achieved in 99% of patients without significant difference between groups (P = 0.38). Conclusion: Our analysis showed the safety and efficacy of surgical lung biopsy with a non-intubated approach in patients affected by lung interstitiopathy. In the context of perioperative risk stratification, obesity would not seem to affect the morbidity compared to normal-weight and overweight patients undergoing this kind of diagnostic surgical procedure.